Retaining Severely Damaged Talar Body and Medial Malleolar Cartilage for Diabetic Ankle/Hindfoot Charcot Arthrodesis Using Intramedullary Nail: A Short Report - Kaissar Yammine MD, PhD; Camille Samaha MD; Chahine Assi MD, MSc (Foot & Ankle Orthopaedics)
Background: The tibiotalocalcaneal (TTC) arthrodesis using an intramedullary nail (IMN) is a common method used to treat advanced diabetic ankle/hindfoot Charcot deformity. The talus is usually resected when severe loss of its body is present and the medial malleolar cartilage excised. We report our initial results with talar retention and absence of medial ankle gutter cartilage debridement. Methods: Four patients with type 2/3A Brodsky classification and stage 2/3 as Eichenholtz classification, presenting with a hindfoot varus deformity were treated with TTC using IMN. The talus was retained after excision of its proximal and distal cartilages while the medial malleolus cartilage was not touched. Bone union was the primary outcome. The minimum follow-up period was 12 months. Results: Bone union was achieved radiologically in all 4 cases within 6 months. No signs of postoperative infection was noted. The mean limb length difference between the pre- and postoperative values was 0.5 ± 0.2 cm. At the final follow-up, all patients were able to walk pain-free with full weightbearing. All 4 patients were very satisfied at 12 months with a mean American Orthopaedic Foot & Ankle Society (AOFAS) ankle-hindfoot score of 87 ± 3.1. Conclusion: When performing TTC arthrodesis for diabetic Charcot, preserving the talus even when the body is severely damaged could add to the stability of the construct resulting in bone healing and some leg length preservation. Including the medial malleolus in the fusion surgery might not be necessary. Level of Evidence: Level IV, case series.